Multi-borehole three-dimensional induced polarization tomography method for tunnel water hazards ahead prospecting - Zhang, Yongheng; Liu, Zhengyu; Bai, Peng; Liu, Bin; Liu, Benchao; Cai, Yumei; Pang, Yonghao (Tunnelling and underground space technology, 2023)
[Display omitted] •We established a multiborehole tomography method to detect water-bearing structures.•We set tunnel configurations to conduct 3D IP measurements/detect geological units.•An IP reference model was constructed for water hazards in front of the tunnel.•The method’s effectiveness was verified based on numerical simulation comparisons.•The method was applied in a drill-and-blast tunnel case in northwest China. Water hazards may lead to some of the most dangerous disasters as the geological circumstances facing tunnel construction are becoming increasingly complex. As a result, more precise detection of water hazards in front of the tunnel is required. Accordingly, a multi-borehole three-dimensional induced polarization (IP) tomography method is proposed herein for tunnel construction. Electric field and sensitivity analyses are presented first, and two IP measurement configurations are then established for the cases in which three or four boreholes are used. For multi-borehole IP detection, two modifications to the IP inversion algorithm are proposed. First, the electrodes’ distance-based data weighting matrix was developed to restrict the inversion's negative effects associated with long-distance current and potential electrodes, and low signal-to-noise ratio (SNR) data. Second, a reference model constraint for water-bearing structures is constructed by utilizing its low-resistivity and high-chargeability characteristics. The multi-borehole three-dimensional IP tomography method was then validated based on numerical simulations. The results reveal that the method is capable of detecting resistivity and chargeability in regions between the tunnel's boreholes in three-dimensional space. The method was also applied in a water diversion tunnel in northwest China, and two water-bearing structures in front of the tunnel were predicted successfully; these outcomes verified the effectiveness of the method.